Soil radon detection using active scintillation cell. Issue 1 (December 2021) - Abdalla, Ayman M.; Ismail, A.M.; Al Madiy, A.A.
ABSTRACT: The paper herein is intended to present the registration efficiency of 300A alpha-scintillation active cell and its application in the field of soil radon detection. In this work, a radon chamber based on a natural radon source has been constructed. This chamber allows calibration of the active scintillation cell under flow-through condition. Radon source has been designed, constructed, and the radon concentration output has been measured. It has been observed that a steady radon concentration can be obtained inside the chamber after a period longer than 30 days. The steady radon concentration inside the chamber is equal to 123.58 Bq/m 3 . It is found that the registration efficiency and the sensitivity of the cell are equal to 0.69 and 1.243 CPM/pCi/l, respectively. After determining the calibration parameters of the cell, soil radon gas survey was carried out in the university city of Najran. It is found that the average radon activity concentration in the tested area is equal to 1332 ± 66 Bq/m 3 . Results of sensitivity and efficiency evaluation, along with radon measurements, are addressed and thoroughly discussed.